Dose response modelling of secretory cell loss in salivary glands using PSMA PET. (December 2022) - Mohan, Vineet; Bruin, Natascha M.; Steenbakkers, Roel J.H.M.; Noordzij, Walter; Terhaard, Chris H.J.; de Keizer, Bart; Al-Mamgani, Abrahim; van de Kamer, Jeroen B.; Sonke, Jan-Jakob; Vogel, Wouter V.
Highlights: The dose response of parotid and submandibular glands as characterised by PSMA PET follows an exponential decay curve. Dose was found to have a relative effect on baseline PSMA. PSMA loss correlated well with patient reported xerostomia during treatment and 1-month post treatment. Substantial PSMA loss was measurable already in the second week of radiotherapy. Abstract: Background and purpose: Xerostomia remains a common side effect of radiotherapy (RT) for patients with head and neck (H&N) cancer despite advancements in treatment planning and delivery. Secretory salivary gland cells express the prostate-specific membrane antigen (PSMA), and show significant uptake on PET scans using 68 Ga/ 18 F-PSMA-ligands. We aimed to objectively quantify the dose–response of salivary glands to RT using PSMA PET. Methods and materials: 28H&N cancer patients received RT with 70 Gy in 35 fractions over 7 weeks. PSMA PET/CT was acquired at baseline (BL), during treatment (DT) and at 1-&6-months post-treatment (PT1M /PT6M ). Dose, BL- PT1M - and PT6M -SUV were extracted for every voxel inside each parotid (PG) and submandibular (SMG) gland. The PT1M/6M data was analysed using a generalised linear mixed effects model. Patient-reported xerostomia and DT-PSMA loss was also analysed. Results: Dose had a relative effect on BL SUV. For a population average gland (BL-SUV of 10), every 1 Gy increment, decreased the PT1M /PT6M -SUV by 1.6 %/1.6 % for PGs and by 0.9 %/1.8 % for SMGs. TD50 of the population curves was 26.5/31.3 Gy for PGs, and 22.9/27.8 Gy for SMGs at PT1M /PT6M . PSMA loss correlated well with patient-reported xerostomia at DT/PT1M (Spearman's ρ = -0.64, −0.50). Conclusion: A strong relationship was demonstrated between radiation dose and loss of secretory cells in salivary glands derived using PSMA PET/CT. The population curve could potentially be used as a dose planning objective, by maximising the predicted post-treatment SUV. BL scans could be used to further tailor this to individual patients.